An Investigation of thermal comfort and assessment of energy consumption in individual vernacular and modern living space - Benkaci, Lydia; Benabbas, Moussadek (Technium Social Sciences Journal, 2022)
The question of the city sustainability was involved in the process of sustainable development, which is considered as guarantees of a harmonious urban development for future generations. The architectural envelope of a living space includes elements that play an important role in energy consumption. The less energy it consumes, the higher energy-efficient it is. Thus, we tried to develop the basic notions and key concepts related to the research topic (energy performance and thermal comfort) of the architectural envelope and then we carried out experimental fieldwork to highlight the link between energy performance and thermal comfort, supported by simulation in order to achieve optimum real results. Our objective is to sort out the issue of energy performance and thermal comfort in living space in both vernacular and contemporary cases, and consequently develop conformations that are as autonomous as possible in terms of energy, by taking advantage of natural inputs and the application of renewable energy for housing. As a result, a survey was carried out on the inhabitants of the houses in the study corpus, and we achieved a qualitative and quantitative work that comes down to an Energetic Performance Diagnosis on a corpus study that constitutes two houses: a vernacular case versus a modern house case. Based on this social survey and energy consumption calculations, we can recommend some guiding points to achieve an architectural conformity that satisfies users’ needs, and reach a long-lasting development on the matter.